2019
DOI: 10.3390/ma12162597
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Reactor Geometry to Manipulate the Properties of Plasma Polymerized Acrylic Acid Films

Abstract: A number of different reactor geometries can be used to deposit plasma polymer films containing specific functional groups and result in films with differing properties. Plasma polymerization was carried out in a low-pressure custom-built stainless steel T-shaped reactor using a radio frequency generator. The internal aluminium disk electrode was positioned in two different geometries: parallel and perpendicular to the samples at varying distances to demonstrate the effect of varying the electrode position and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…For the C1s spectrum of the two samples in Fig. 3d, three signals located at 289 eV, 286 eV and 284.8 eV correspond to the C=O, C-O, C-C/C-H, respectively, indicating the existence of oxygen-containing functional groups such as carboxyl group [42,43] and in consistent with the results from FTIR.…”
Section: Resultssupporting
confidence: 82%
“…For the C1s spectrum of the two samples in Fig. 3d, three signals located at 289 eV, 286 eV and 284.8 eV correspond to the C=O, C-O, C-C/C-H, respectively, indicating the existence of oxygen-containing functional groups such as carboxyl group [42,43] and in consistent with the results from FTIR.…”
Section: Resultssupporting
confidence: 82%
“…Higher electron flux likely results in greater monomer fragmentation, which produces higher deposition rates and greater film cross linking. [42] As the 0° samples deposited at 20 W and 80 mm from the electrode still showed a decrease in film thickness after water immersion, it can be suggested that an electron flux of ≥ 80 A/m 2 is required to produce stable ppAAc films. Such behavior indicates that O/C ratios lower than 0.4 are required for film stability not to be significantly compromised.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…For distances from the electrode of 30 -80 mm and shorter probe travel distances, the electron flux decreases indicates reduced electron collisions further from the electrode, which has previously been reported in our research. [24,42] The decrease in the electron flux as the probe travels closer to the electrode at 15 mm is due to the probe travelling through the plasma sheath region, which is deficient of energetic electrons. [22] This article is protected by copyright.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…[19] The effects of plasma deposition on membrane surfaces can be controlled by variation of parameters such as treatment time, duty cycle, power of the plasma source (wattage), type of gas, flow rate, and others. [20][21][22][23][24][25][26] It is well known that plasma polymerization is an environmentally friendly process and is considered one of the most promising technologies for preparing thin films with functional groups and desirable properties. [27,28] These films are rigid.…”
Section: Introductionmentioning
confidence: 99%